The Management of Valgus Extension Overload Syndrome Experienced with Hitting in a High School Baseball Player: A Case Report - Andrew B Piraino; Brent M Davis (North American Sports Medicine Institute, 2022)
# Background Valgus extension overload syndrome (VEOS) of the elbow is a condition associated with overhead athletes. However, the non-surgical management of these individuals is not well documented. # Purpose To discuss the unique presentation, management, and outcomes of an adolescent baseball player with a chronic history of VEOS experienced during hitting. # Case Description A 15-year-old right-handed high school baseball catcher presented with a six-month history of right-sided ulnar elbow pain. Elbow MRI w/ contrast was consistent with VEOS. The initial examination demonstrated excessive resting right-sided humeral external rotation compared to his left. Valgus stress testing in the subject's hitting position reproduced symptoms, which were alleviated with retest while correcting excessive humeral external rotation. Weakness of the humeral internal rotators and stiffness/shortness of the posterior shoulder were found and thought to relate to the humeral contribution to his elbow movement dysfunction. Rehabilitation emphasized addressing impairments contributing to excessive humeral external rotation with reintegration into batting. # Outcomes After five weeks of physical therapy, the subject returned to soft toss hitting at approximately 75% velocity for the first time since symptom onset, without pain. At seven months after discharge, a phone conversation confirmed that the subject had returned to baseball without limitations. # Discussion Despite the concept of 'regional interdependence', common proximal impairments are often assumed to contribute to elbow pain without a clear biomechanical rationale. Future research demonstrating the specific biomechanical effects of the shoulder on the elbow is needed, in addition to more accessible examination strategies to assess their relationship. # Level of Evidence 5